(untitled) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study explores how Office Administration students at Politeknik Pajajaran ICB Bandung demonstrate innovation and creativity in developing digital-based entrepreneurial projects. Through a qualitative descriptive approach involving interviews with ten students who have established digital businesses, the research identifies key factors that drive their success: creative thinking, digital literacy, and experiential learning through project-based courses such as Digital Business, Business Planning, and Digital Product Design. Findings reveal that students’ creativity and innovative behavior are strongly influenced by the integration of digital learning environments and mentoring systems. These educational elements foster students’ confidence and ability to transform ideas into sustainable online ventures. The study contributes to understanding how vocational education can cultivate entrepreneurial competencies aligned with the demands of the digital economy.